2019
DOI: 10.1039/c9cc06838d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient green light-excited switches based on dithienylethenes with BF2-doped π-conjugated systems

Abstract: Novel dithienylethene derivatives with BF2-doped π-conjugation show efficient green light-excited photoswitching behaviors in solvents, PMMA film and living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Moreover, visible light‐driven switching of fluorescence has been observed in this luminescent compound. The fluorescent switching behavior of the compound has also been effectively achieved in living cells [120] . Compound 44 has been made to respond to visible light by extending π‐conjugation with electron donating groups [121] .…”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
“…Moreover, visible light‐driven switching of fluorescence has been observed in this luminescent compound. The fluorescent switching behavior of the compound has also been effectively achieved in living cells [120] . Compound 44 has been made to respond to visible light by extending π‐conjugation with electron donating groups [121] .…”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
“…A. eine relativ hohe Elektronenaffinität [17], sodass sie z. B. als p-Dotanden zur Er-höhung der elektrischen Leitfähigkeit von organischen Verbindungen [18] -üblicherweise als organische Metalle bezeichnet -, zur Sensibilisierung von über Radikalionen ablaufende fotochemische Reaktionen [19] oder als Fotosensibilisatoren in elektrofotografischen Materialien eingesetzt werden können [20]. [23,24] sowie von organischen Schwefelverbindungen [25] sowie von Pikrinsäure [26].…”
Section: Besondere Extinktionskoeffizientunclassified
“…Accordingly, it was found that dithienylethene 1 exhibited solvent-dependent photochromic properties, which was in accordance with other BF 2 bdkcontaining dithienylethenes reported recently. [23][24][25][26][27][28] Upon alternating irradiation with blue/red light, the fluorescent switching behavior was also investigated in the above solvents at room temperature. As depicted in Figure 4(a), its luminescence intensity at 580 nm in CH 2 Cl 2 gradually decreased along with an obvious fading of the red fluorescence, which was due to efficient energy transfer from the excited difluoroboron β-diketonate moiety to the ringclosed dithienylethene skeleton.…”
Section: Optical Switching Behaviormentioning
confidence: 99%
“…[18][19][20][21][22] In consideration of their intriguing photophysical properties, our group has recently designed and synthesized a range of visible light-responsive difluoroboron β-diketonate (BF 2 bdk) complexes, based on a diarylethene unit via Knoevenagel condensation reactions. [23][24][25][26][27][28] Most of the obtained complexes demonstrated excellent visible light-controlled photochromic properties and fluorescence switching behavior in solution, polymethyl methacrylate (PMMA) film, and even in living cells. However, these asymmetric BF 2 bdk-functionalized dithienylethene derivatives normally required non-trivial multistep syntheses.…”
Section: Introductionmentioning
confidence: 99%